Advocating for sexual rights at the UN: the unfinished business of global development. Issue 46 (November 2015) - Ali, Saida; Kowalski, Shannon; Silva, Paul
Abstract: Twenty years ago, governments agreed that the right to have control over and decide freely and responsibly on all matters related to one's sexuality, free from coercion, discrimination and violence, is a fundamental human right. Since then, many aspects of sexual rights have been agreed by consensus at the global level, but the term "sexual rights" itself continues to be removed from negotiated outcomes and left out of international agreements, often at the last stages of negotiations. This commentary represents our point of view on the unfinished business of the UN with regards to the fight for sexual rights. Our perspective draws from lessons learned in cross-movement organizing in various regional UN spaces and outlines some of the tactics by conservative forces to push sexual rights to the periphery. The article reaffirms the position that broadening the debate and concepts surrounding sexual rights to be more inclusive, has enormous transformational potential and should inform collective advocacy efforts moving forward. Résumé: Il y a 20 ans, les gouvernements ont convenu que le droit de maîtriser sa sexualité et de décider librement et de manière responsable de toutes les questions s'y rapportant, sans coercition, discrimination ni violence, est un droit de l'homme fondamental. Depuis, beaucoup d'aspects des droits sexuels ont été adoptés par consensus au niveau international, mais le terme « droits sexuels » continue d'être supprimé des résultats négociés et écarté des accords internationaux, souvent dans les derniers stades de la négociation. Ce commentaire présente notre point de vue sur le travail inachevé des Nations Unies en ce qui concerne la lutte pour les droits sexuels. Notre perspective se fonde sur les leçons tirées de l'organisation de mouvements dans différents espaces régionaux des Nations Unies et souligne certaines des tactiques employées par les forces conservatrices pour marginaliser les droits sexuels. L'article réaffirme la position selon laquelle l'élargissement du débat et des concepts entourant les droits sexuels afin d'être plus inclusifs possède un formidable potentiel de transformation et devrait guider les activités collectives de plaidoyer pour aller de l'avant. Resumen: Hace veinte años, los gobiernos acordaron que el derecho de tener control sobre todo lo relacionado con la sexualidad propia, y de decidir libre y responsablemente al respecto, sin coacción, discriminación y violencia, es un derecho humano fundamental. Desde entonces, muchos aspectos de los derechos sexuales han sido acordados por consenso a nivel mundial, pero el término "derechos sexuales" continúa siendo eliminado de los resultados negociados y omitido de los acuerdos internacionales, a menudo en las últimas etapas de las negociaciones. Este comentario representa nuestro punto de vista sobre los asuntos pendientes de las Naciones Unidas con respecto a la lucha por los derechos sexuales. Nuestra perspectiva se basa en lecciones aprendidas en la organización de movimientos en diversos espacios regionales de las Naciones Unidas y resume algunas de las tácticas por fuerzas conservadoras para empujar los derechos sexuales hacia la periferia. El artículo reafirma la postura de que ampliar el debate y los conceptos relacionados con los derechos sexuales para ser más inclusivo, tiene un enorme potencial transformativo y debe informar los esfuerzos colectivos de promoción y defensa de aquí en adelante.